Answer:
the answer is 3
Step-by-step explanation:
(-5x-3)(-5x+3)=(5x)^2 - (3)^2
A difference of squares is the difference of two squared terms.
We have
a^2 - b^2
We can factorize the difference of squared terms like this:
a^2-b^2 = (a+b)(a-b)
We have (-5x-3)(-5x+3)
Lets prove it:
(-5x-3)(-5x+3) = (-5x*-5x)+(-5x*3)+(-3*-5x)+(-3*3)
(-5x-3)(-5x+3) = 25x^2+(-15x)+(15x)+(-9)
(-5x-3)(-5x+3) = 25x^2-15x+15x-9
(-5x-3)(-5x+3) = 25x^2-9
(-5x-3)(-5x+3) = (5x)^2 - (3)^2
Answer: I would go with C
Step-by-step explanation: if correct please mark brainliest
It's not a as flip is rotational, turn can also be rotational. I would go with slide as translation is a sideways motion
Step-by-step explanation:
(11.99+23.98+9.95)= 45.92
she has to pay = 45.92 - 20/100 (45.92)
= 45.92 - 9.18 = 36.74
so option
about 37 is right
Answer:
i think this may help you